Distribution and natural variation of free, esterified, glycosylated, and insoluble-bound phenolic compounds in brocade orange (Citrus sinensis L. Osbeck) peel. (March 2022) - Wang, Zhirong; Chen, Xuhui; Guo, Zehang; Feng, Xiya; Huang, Pimiao; Du, Muying; Zalán, Zsolt; Kan, Jianquan
Graphical abstract: Highlights: Phenol profiles were affected by growth stage, peel tissue, and phenolic forms. Generally, phenols in both flavedo and albedo evidently decreased during ripening. Phenol levels in the flavedo adhered to the trend: EBPs > GBPs ≈ FPs ≫ IBPs. Phenol levels in the albedo adhered to the trend: GBPs ≫ FPs ≈ EBPs ≫ IBPs. Ferulic acid, hesperetin, and hesperidin were the major variable metabolites. Abstract: Brocade orange ( Citrus sinensis L. Osbeck) peel, a by-product which is usually discarded in large amounts, is rich in a broad spectrum of phenols. Accordingly, this study investigated the distribution and natural variation of free, esterified, glycosylated and insoluble-bound phenols (FPs, EBPs, GBPs, and IBPs) in the peels. Regardless of phenolic fraction or peel position, the total phenol and flavonoid contents, and most tested phenolic compound contents were generally abundant during the immature and semi-mature stages but existed at lower levels during the commercial mature period. The flavedo was much richer than the albedo in a few phenolic acids, flavonols, flavones, and especially polymethoxyflavonoids, which was particularly true for EBPs. Flavanones, particularly in GBP form, were generally present in equal or even much higher levels in the albedo. The four phenolic forms exhibited distinct trends in terms of abundance. In the flavedo (except the young fruit stage) followed the order: EBPs > GBPs ≈ FPs ≫ IBPs, and in the albedo: GBPs ≫ FPs ≈ EBPs ≫ IBPs. Generally, the phenols examined for this study were highly abundant in the citrus peels, endowing this agricultural waste with great potential to be an excellent natural source of functional ingredients.